The Effect of Core Stability Training on Jump Serve Accuracy in Youth Volleyball Players - Bujang; Aridhotul Haqiyah; Mia Kusumawati; Arisman (Universitas Negeri Semarang, 2025)
The purpose of this study was to examine the effect of core stability training on jump serve accuracy in adolescent volleyball players. In the sport of volleyball, jump serve accuracy is essential for creating effective attacks, while core stability plays an important role in controlling body movement, improving balance, and generating the strength needed to serve accurately. This study used an experimental design with 30 youth volleyball players from the New Antarctica Club who were divided into two groups: an experimental group that underwent a 6-week core stability training program and a control group that received no specific training intervention. The results showed that the experimental group experienced a better and significant improvement in jump serve accuracy compared to the control group. Therefore, it can be concluded that core stability training can improve jump serve accuracy in adolescent volleyball players.